Cell extrusion drives neural crest cell delamination - Emma L. Moore Zajic; Ruonan Zhao; Mary C. McKinney; Kexi Yi; Christopher Wood; Paul A. Trainor (Proceedings of the National Academy of Sciences, 2025)
Neural crest cells (NCC) comprise a heterogeneous population of cells with variable potency that contribute to nearly every tissue and organ throughout the body. Considered unique to vertebrates, NCC are transiently generated within the dorsolateral region of the neural plate or neural tube during neurulation. Their delamination and migration are crucial for embryo development as NCC differentiation is influenced by their final resting locations. Previous work in avian and aquatic species revealed that NCC delaminate via an epithelial–mesenchymal transition (EMT), which transforms these progenitor cells from static polarized epithelial cells into migratory mesenchymal cells with fluid front and back polarity. However, the cellular and molecular mechanisms facilitating NCC delamination in mammals are poorly understood. Through time-lapse imaging of NCC delamination in mouse embryos, we identified a subset of cells that exit the neuroepithelium as isolated round cells, which then halt for a short period prior to acquiring the mesenchymal migratory morphology classically associated with delaminating NCC. High-magnification imaging and protein localization analyses of the cytoskeleton, together with measurements of pressure and tension of delaminating NCC and neighboring neuroepithelial cells, revealed that round NCC are extruded from the neuroepithelium prior to completion of EMT. Furthermore, cranial NCC are extruded through activation of the mechanosensitive ion channel, PIEZO1. Our results support a model in which cell density, pressure, and tension in the neuroepithelium result in activation of the live cell extrusion pathway and delamination of a subpopulation of NCC in parallel with EMT, which has implications for cell delamination in development and disease.